Design of Information and Communication Technology Teaching Materials Based on Contextual Teaching and Learning - Vidya Octavianti (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
SMP Patra Mandiri 2 Palembang is an educational institution affected by the COVID-19 pandemic, which disrupted face-to-face learning activities. Consequently, the entire learning process was conducted online. The situation underscored the critical role of teaching materials in facilitating effective learning. Teaching materials are instructional resources designed in accordance with the curriculum to achieve established competency standards and learning objectives. In the Information and Communication Technology (ICT) subject, teaching and learning are generally carried out in computer laboratories, where teachers rely on printed manuals to guide students during practical sessions. This conventional approach limits the delivery of updated knowledge. Therefore, a web-based system for developing ICT teaching materials was designed using the Contextual Teaching and Learning (CTL) model. CTL emphasizes connecting academic content with real-world situations to enhance students’ understanding and engagement. The research resulted in a web-based ICT teaching material platform grounded in CTL principles. The system serves as an effective medium for online learning, providing teachers with an efficient tool to deliver instructional materials and students with flexible access to learning resources.